Peranan Koperasi Pondok Pesantren Miftahul Ulum dalam Memberdayakan Ekonomi Masyarakat Desa Pesisir Kecamatan Sumberasih – Probolinggo - Abdul Hamid (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2015)
In this research, Kopontren discuss the idea of Kopontren rolein empowering peoples economy empowerment programs through the loanand save it for the society stores / minimarts, also using a cyber cafe topeople about boarding finally can be achieved with both the welfare of thesurrounding community and Kopontren where Kopontren has strategicrole in the increased business as a member of islamic cooperation that, andgood management of the savings from the bank capital. However, thereare some people who think that Pesisir Kopontren still unable to providemaximum service and business services for residents. The research that weuse is a case study in Kopontren Miftahul Ulum Pesisir with the actualdata in the interview techniques (interview) and direct observation.Besides, we also use of the library to become as a reference for research.It appears that the success of the business Kopontren Miftahul Ulum theloan and save is this program could provide a solution to develop businessin a run by members of the public to empower villagers Pesisir in order tobecome partners Kopontren Miftahul Ulum. Therefore comes a businessmodel Kopontren project program through an increase in loan and saveto improve services, and cyber cafe and also to increase distribution to theminimarts in hopes can become an inspiration for the parties involvedand cooperatives (Kopontren) in the field.